2008
DOI: 10.1111/j.1475-6803.2008.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

The Investment Opportunity Set and Its Proxy Variables

Abstract: We use a real options approach to evaluate the performance of several proxy variables for a firm's investment opportunity set. The results show that, on a relative scale, the market-to-book assets ratio has the highest information content with respect to investment opportunities. Although both the market-to-book equity and the earnings-price ratios are related to investment opportunities, they do not contain information that is not already contained in the market-to-book assets ratio. Consistent with this find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
151
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(156 citation statements)
references
References 33 publications
2
151
0
3
Order By: Relevance
“…Where EARN it+1 is the one-year-ahead net income before extraordinary items are scaled by the beginning of total assets; EARN is the current net income before extraordinary items are scaled by the beginning of total assets; SFCF is a binary variable with the value of one if FCF (see Equation [2]) is above the sample median for the year and the growth prospects (MBR) is below the sample median for the year, and zero if otherwise; BDIND_DUM is a binary variable with the value of one, if board independence equals or more than 33%, and zero if otherwise; BDSIZE is the total number of directors on the board; CHIND is a binary variable with the value of one (zero if otherwise), if the board chairman is an independent director; LNZISE is the natural log of book value of the total firm assets; DEBT is the long-term debt to the total assets; LOSS is a binary variable with the value of one for the loss firms, and zero for other firms; CAP is the depreciation, depletion, and amortization expense scaled by the total sales; and ε is the error term.…”
Section: Methodsmentioning
confidence: 99%
“…Where EARN it+1 is the one-year-ahead net income before extraordinary items are scaled by the beginning of total assets; EARN is the current net income before extraordinary items are scaled by the beginning of total assets; SFCF is a binary variable with the value of one if FCF (see Equation [2]) is above the sample median for the year and the growth prospects (MBR) is below the sample median for the year, and zero if otherwise; BDIND_DUM is a binary variable with the value of one, if board independence equals or more than 33%, and zero if otherwise; BDSIZE is the total number of directors on the board; CHIND is a binary variable with the value of one (zero if otherwise), if the board chairman is an independent director; LNZISE is the natural log of book value of the total firm assets; DEBT is the long-term debt to the total assets; LOSS is a binary variable with the value of one for the loss firms, and zero for other firms; CAP is the depreciation, depletion, and amortization expense scaled by the total sales; and ε is the error term.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the life cycle classification procedure employed in this study is based on [23] with some modifications to take into account the requirements and scope of this study. Based on previous studies (for example, [24], [25]), three proxy variables are selected to be used for the firm life cycle stage…”
Section: Firm Life Cycle Classification Methodologymentioning
confidence: 99%
“…Ahmed et al (2002) and Li (2010) used research and development expenditures to measure increased investment. However, Adam and Goyal (2008) discussed alternative measures of investment opportunity and have suggested that CAPX is also a good proxy for investment opportunity. We chose to use the CAPX ratio because research and development costs were not separately listed for the Chinese companies in the database.…”
Section: Accrual-based Measure Of Conservatismmentioning
confidence: 99%